Risks in Modern Society - Bischoff, Hans-Jürgen (Topics in Safety, Risk, Reliability and Quality, 2008)
Risks in a changing and global world are complex and interconnected, even more so in a globalized world consisting of many societies at very different levels of development. Work life is strongly influenced by all forms of globalization - for example, the growing gap between rich and poor; demographic transition towards ageing or very young societies; growing mobility of people; the rapid diffusion of new technologies and a variety of working and environmental conditions in highly industrialized and developing countries; let alone rapidly changing economic structures including new types of enterprises and occupations. Good governance for handling occupational safety, population health and environmental quality has become one of the decisive criteria for ensuring competitive business structures, quality performance and high motivation by workers, excellent conditions of public health and societal well-being and functioning of corporate and community policies and services. Furthermore, risk governance is crucial for sustainable development, the preservation of diverse life styles, and social cohesion. Social networks, cultural and religious as well as political and media environments benefit from a system in which threats to safety, health and the environment are well taken care of. Occupational safety and health is an important public good, and a prerequisite for effective and enduring social security systems. The main goal of this book is to make the reader familiar with the complexity and multi-dimensionality of the subject RISK, focusing on the changing character of work in a globalised economy. The main emphasis is on providing practical guidelines for improved risk governance, i.e., how to find adequate solutions through integrated methods of risk assessment, risk handling and risk communication for the benefit of everyone: employers, workers, other stakeholders as well as shareholders and society at large.